CLINICAL COURSE AND DIAGNOSTIC CRITERIA OF VARICOCELE: A THEORETICAL AND EVIDENCE-BASED ANALYSIS (International journal of medical sciences, 2026)
Varicocele is a common vascular abnormality of the pampiniform plexus characterized by venous dilatation and reflux within the spermatic cord. It affects approximately 15% of the general male population and up to 35–40% of men with primary infertility. Despite its high prevalence, the clinical course of varicocele varies widely, ranging from asymptomatic cases to progressive testicular dysfunction and impaired fertility. The condition most frequently develops during adolescence and early adulthood, coinciding with pubertal hemodynamic changes. Pathophysiological mechanisms include increased scrotal temperature, oxidative stress, hypoxia, hormonal dysregulation, and altered microcirculation. Clinically, patients may present with scrotal discomfort, testicular asymmetry, or infertility, although many remain asymptomatic. Diagnostic evaluation relies on physical examination, including the Valsalva maneuver, and is complemented by Doppler ultrasonography to confirm venous dilatation and reflux. Standardized grading systems and imaging criteria are essential to ensure diagnostic consistency. The challenge lies in distinguishing clinically significant cases from subclinical findings to avoid overtreatment while preventing long-term reproductive damage. This article synthesizes contemporary scientific evidence on the natural history and diagnostic standards of varicocele, emphasizing objective clinical assessment, imaging thresholds, and risk stratification. An evidence-based approach to diagnosis is fundamental to optimizing patient outcomes and preserving male reproductive health.